Combined application of nutrients improves fruit quality of sapota (Acharas zapota) cv. kalipatti - MEENA, HEM RAJ; KAUSHIK, RAM AVATAR; T S, CHAITHRA; MEENA, MEENAKSHI; J, SOMASUNDARAM; KALA, S; SHARMA, GULSHAN; KUMAR, ASHOK; ALI, SHAKIR; MEENA, GOPAL LAL; KUMAR, KULDEEP; MEENA, OM PRAKASH (The Indian Journal of Agricultural Sciences, 2026)
The current study was performed at ICAR- Indian Institute of Soil and Water Conservation (IISWC), Research Farm, Kota, Rajasthan during July to May 2020–21 and 2021–22 on sapota (Acharas zapota) cv. Kalipatti to appraise the impact of chemical, organic and biological fertilisers on quality production of sapota fruits. Indiscriminate use of inorganic fertilisers are threat to environment coupled with adverse effects on quality of produce and soil health. Integrated nutrient management (INM) can fulfill the nutrients need of the sapota plants for qualitative and quantitative produce and reduce the need of chemical fertilisers. A field study was conducted with 17 different treatment combinations, including farm yard manure (FYM), vermicompost, recommended dose of fertilisers (RDF) and biofertilisers. The findings of conducted field trial revealed that integration of RDF 75% + VC 10 kg + AZS 250 g + AZB 250 g/plants recorded higher fruit diameter (5.67 cm), length of fruit (6.20 cm) and weight of fruit (100.17 g). Beside this, higher fruit firmness (4.96 kg/cm2) and pulp: seed ratio (93.09) was recorded in the same treatment. Although, biochemical parameters for instance total soluble solids (20.05 0B), ascorbic acid (11.86 mg/100 g pulp), TSS: acid ratio (121.29) and reducing sugar (5.11%) were recorded in treatment having RDF 75% + FYM 50 kg + AZS 250 g + AZB 250 g/plant. The impact demonstrated that applying two-thirds of the recommended quantity of inorganic fertilisers i.e. 1000 g, 500 g and 500 g NPK/plant in sapota cv. kalipatti enhanced total soluble solids (TSS) content (9.68%) and fruit weight (13.72 %) over the control.